First record of Oceanic Anoxic Event 2 in the Eastern Carpathians: implications for chemostratigraphic and biostratigraphic correlations - Melinte-Dobrinescu, Mihaela; Ion, Gabriel; Anton, Eliza; Apotrosoaei, Vlad; Briceag, Andrei; Lazăr, Constantin (Frontiers in Earth Science, 2023)
This study aims to investigate a marlstone and claystone succession located at the southern end of the Eastern Carpathians, a region where oceanic anoxic event 2 (OAE2) has not been pointed out so far. Toward the upper half of this succession, a 17-cm-thick black shale was identified. The investigated depositional interval lies within the late Cenomanian–early Turonian, encompassing the UC3d up to UC7 nannofossil zones. The δ13C values fluctuated between 2.06‰ and 3.89‰, showing a positive isotope excursion that was assigned to OAE2. The δ13C isotope curve displays the following intervals: pre-excursion, first build-up, trough, second build-up, plateau, and post-excursion. Within the second build-up interval of OAE2, a substantial shift in CaCO3 values, accompanied by high concentrations of total organic carbon and a significant decline in the abundance and diversity of calcareous nannofossil assemblages, was observed. The nannofossil turnover related to OAE2 climax revealed predominance of Watznaueria barnesiae and temporary disappearance from the record of surface-water higher fertility taxa, such as Biscutum constans, Zeugrhabdotus erectus, and Discorhabdus ignotus. Above OAE2, peaks of Eprolithus floralis, followed by increased abundance of Eiffellithus turriseiffelii and Nannoconus spp., were identified. In the lower part of the studied succession (i.e., the upper Cenomanian UC3d nannofossil subzone), during the pre-excursion characterized by low δ13C values and less negative δ18O values, a small group of nannofossils more related to mid- and high-paleolatitudes, such as Crucibiscutum salebrosum, Repagulum parvidentatum, and Seribiscutum primitivum, is present, always showing a low abundance.